Exercise imagery and its correlates in older adults - Thøgersen-Ntoumani, Cecilie; Cumming, J.; Ntoumanis, Nikos; Nikitaras, N. (Elsevier BV, 2012)
Objectives: The purpose of the present study was to test a structural model examining the interrelationships between exercise imagery, self-reported exercise behaviour and well-being in older adults. Design: Cross-sectional survey. Method: Participants were 499 older Greek adults (50.10% males) aged between 51 and 84 years (M age = 57.31; SD = 5.52) who completed questionnaires measuring exercise imagery use, exercise behaviour, subjective vitality, and physical self-worth. The relationship between these variables was tested with a structural model based on the applied model of imagery use for exercise ( Munroe-Chandler & Gammage, 2005). Results: Energy imagery positively predicted exercise behaviour and subjective vitality, and appearance and technique imagery positively predicted physical self-worth. Conclusions: These results indicate older adults engage in different types of imagery to motivate themselves to exercise and improve their well-being, thus implying that the content of imagery interventions should be specifically tailored to the outcomes older adults wish to realise for interventions to be effective.